2022
DOI: 10.1177/17534666221091183
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled asthma predicts severe COVID-19: a report from the Swedish National Airway Register

Abstract: Background: Severe asthma increases the risk of severe COVID-19 outcomes such as hospitalization and death. However, more studies are needed to understand the association between asthma and severe COVID-19. Methods: A cohort of 150,430 adult asthma patients were identified in the Swedish National Airway Register (SNAR) from 2013 to December 2020. Data on body mass index, smoking habits, lung function, and asthma control test (ACT) were obtained from SNAR, and uncontrolled asthma was defined as ACT ⩽19. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…One study using Swedish National Airway Register showed that patients with uncontrolled asthma and high disease burden, including increased asthma medication intensity, would be associated with an increased risk of severe COVID-19. 6 Similar findings were demonstrated in another national incident cohort study in Scotland. 3 …”
supporting
confidence: 81%
“…One study using Swedish National Airway Register showed that patients with uncontrolled asthma and high disease burden, including increased asthma medication intensity, would be associated with an increased risk of severe COVID-19. 6 Similar findings were demonstrated in another national incident cohort study in Scotland. 3 …”
supporting
confidence: 81%
“…Our search yielded nine studies that quantified the association between severe asthma and poor COVID-19 outcomes (Table 1 ) [ 16 , 17 ▪ , 18 ▪ , 19 23 , 24 ▪ ]. Each of these studies used a unique definition of severe asthma, based on: the number and/or type of medicines used to control asthma, the Global Initiative for Asthma (GINA) severity level, recent history of severe asthma exacerbation, or an Asthma Control Test (ACT) score ≤19, the latter a measure of uncontrolled asthma.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 14 studies that examined COVID-19 showed mixed results (Fig. 3 ) [ 17 ▪ , 18 ▪ , 22 , 23 , 24 ▪ , 26 , 30 37 ]. ICS use in patients with asthma was associated with increased odds (OR = 1.20, 1.08–1.34) of COVID-19 (nonfatal) severity, but decreased odds of COVID-19 mortality (OR = 0.89, 95% CI 0.86–0.92).…”
Section: Resultsmentioning
confidence: 99%
“…Airway remodeling is an essential feature of asthma, manifested by structural changes in the airways, such as basement membrane thickening, bronchial fibrosis, airway smooth muscle cell hyperplasia, and hypertrophy ( 6 8 ). Among COVID-19 patients, uncontrolled asthma was identified as contributing factor to mortality, and patients also had more severe asthma manifestations during the pandemic ( 9 , 10 ). Therefore, considering the current COVID-19 epidemic and the high prevalence of asthma, the study results are timely.…”
Section: Introductionmentioning
confidence: 99%